1995
DOI: 10.1046/j.1365-2648.1995.21050820.x
|View full text |Cite
|
Sign up to set email alerts
|

The need for and process of collaborative international research: a replication study of Japanese staff nurse perceptions of head nurses' actions

Abstract: Despite differences between countries, people's health needs are similar, as are nursing problems and issues Collaborative nursing research is needed to identify similarities and differences among countries Visiting researcher(s), however, must understand the host country's culture and traditions to avert exploitation and misunderstanding Collaborative research should enhance nursing in each country The authors describe a replication study, in a Japanese hospital, of nursing administration research previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Translation and validation of research questions are crucial moments in international research to ensure that results are due to real differences and not errors in translation (Schmieding & Kokuyama 1995, Maneesriwongul & Dixon 2004). The original Swedish version of the questionnaire was developed and tested in previous Swedish studies among formal carers (Saveman 1994, Saveman & Hallberg 1997).…”
Section: The Studymentioning
confidence: 99%
“…Translation and validation of research questions are crucial moments in international research to ensure that results are due to real differences and not errors in translation (Schmieding & Kokuyama 1995, Maneesriwongul & Dixon 2004). The original Swedish version of the questionnaire was developed and tested in previous Swedish studies among formal carers (Saveman 1994, Saveman & Hallberg 1997).…”
Section: The Studymentioning
confidence: 99%
“…The need for global exchange of knowledge and competences among healthcare professionals has never been greater (Schmieding & Kokuyama 1995, Leininger 1997a,b, Irvine et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Translation strives to achieve conceptual equivalence (Schmieding & Kokuyama, 1995;Mason, 2005). "Conceptual equivalence implies that an item may be translated into different words, but the original meaning or conceptual framework remains intact" (Mason, 2005 t cannot be assumed that all students are as familiar with multiple choice items as U.S. students" (p. 4).…”
Section: Translation Protocol In the Literaturementioning
confidence: 99%
“…"Conceptual equivalence implies that an item may be translated into different words, but the original meaning or conceptual framework remains intact" (Mason, 2005 t cannot be assumed that all students are as familiar with multiple choice items as U.S. students" (p. 4). The issues must be addressed in both cross-cultural research and intercultural research using translated instruments, to avoid differences found being attributed to groups when they are actually caused by errors in translation (Schmieding & Kokuyama, 1995).…”
Section: Translation Protocol In the Literaturementioning
confidence: 99%
See 1 more Smart Citation